A Study of Teachers’ Perceptions of the Principal’s Leadership Style and Their Job Satisfaction at Nelson English Language Centre, Yangon, Myanmar - Chan, Pont Pont Nyein (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
This study explores the relationship between principal leadership styles and teachers’ job satisfaction at Nelson English Language Centre in Yangon, Myanmar. Grounded in transformational and transactional leadership theories, Maslow’s Hierarchy of Needs, and Herzberg’s Two-Factor Theory, a quantitative methodology was employed. Data were collected via surveys from 80 teachers. Findings revealed that teachers perceived their principal’s leadership style as primarily transformational, with a mean score of 3.18 on a five-point scale, while their job satisfaction was rated moderately high, averaging 3.45. Statistical analysis showed a significant positive correlation between transformational leadership and job satisfaction (r = 0.68, p < 0.01) and a moderate positive correlation with transactional leadership (r = 0.52, p < 0.05). These results suggest that transformational leadership practices—such as inspirational motivation, intellectual stimulation, and individualized consideration—are closely linked to higher teacher satisfaction. School leaders are encouraged to adopt more transformative approaches to foster supportive, motivating environments that enhance teacher morale and retention. This research adds valuable insights to the limited literature on educational leadership and job satisfaction in Myanmar’s private language schools. It highlights the critical role of leadership styles in promoting organizational effectiveness.